Manganese Utilization in Salmonella Pathogenesis: Beyond the Canonical Antioxidant Response - Uppalapati, Siva R.; Vazquez-Torres, Andres (Frontiers in Cell and Developmental Biology, 2022)
The metal ion manganese (Mn2+) is equally coveted by hosts and bacterial pathogens. The host restricts Mn2+ in the gastrointestinal tract and Salmonella-containing vacuoles, as part of a process generally known as nutritional immunity. Salmonella enterica serovar Typhimurium counteract Mn2+ limitation using a plethora of metal importers, whose expression is under elaborate transcriptional and posttranscriptional control. Mn2+ serves as cofactor for a variety of enzymes involved in antioxidant defense or central metabolism. Because of its thermodynamic stability and low reactivity, bacterial pathogens may favor Mn2+-cofactored metalloenzymes during periods of oxidative stress. This divalent metal catalyzes metabolic flow through lower glycolysis, reductive tricarboxylic acid and the pentose phosphate pathway, thereby providing energetic, redox and biosynthetic outputs associated with the resistance of Salmonella to reactive oxygen species generated in the respiratory burst of professional phagocytic cells. Combined, the oxyradical-detoxifying properties of Mn2+ together with the ability of this divalent metal cation to support central metabolism help Salmonella colonize the mammalian gut and establish systemic infections.